(3GdUOQjIs
(3ChdgG (B:s
(3CeG HYO, deG CdaJ GdbhGYO GdfMhjI hSejJgG HGdQSGdI GdTeSjI s
(3BNQgG (B:s
(3hbO jchf HeYfi GdMb fMh (B"(3cdG Ef GdEfSGf djWZi(B" (3aEf cdG ajg HeYfi GdMb hbO hbY GdEJeGe HGdMb s
(3fSNI KGfjI JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGX haj BNQgG HGNJdGa aj HYV GdCdaGX hHYV SbW aj GdYHGQGJs
(3HgG fXGe GdJYbjHIs
(3hHYV GdWjGQGJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs